An exploratory case study of a Lebanese e-learning partnership model. (20th March 2006) - Feghali, Tony; Martin, Marc; Sahyoun, Najib
Globally, distance learning programmes have become an increasingly popular method to enhance knowledge and skills, particularly online learning at the academic level for courses, programmes and degrees. However, the 'digital divide' conditions that exist often make its development problematic for developing countries. Hence, this case study presents and examines a proposed e-learning partnership model involving various societal institutions regarding its risks, benefits and outcomes, along with roles and responsibilities. Moreover, the study discusses critical issues and activities that appear necessary for its development and implementation.